1971
DOI: 10.1346/ccmn.1971.0190507
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Lithium Exchange Equilibria on Vermiculite at 25° and 50°C

Abstract: Abstract-Sodium-lithium exchange equilibria between dilute aqueous chloride solutions and 0.2-62/z Transvaal, South African vermiculite were studied at 25 ~ and 50~ using a dialysis technique. The K content of the vermiculite was reduced to < 1% of the exchange capacity of 2.14 me/g by exhaustive extraction using Na-tetraphenylboron. The thermodynamic equilibrium constants and in turn the standard free energies and heats of exchange were evaluated from the equilibrium selectivity coefficients at the two temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 15 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…This is in agreement with previous study which also showed that the quantity of water released was 9 more than expected from the dehydroxylation of vermiculite itself [43]. In K-vermiculite, all typical vermiculite features had disappeared and the lattice had drastically collapsed [7]. By the same token, the typical well-ordered mica-like structure reflection at 2θ = 8.74° (10.10 nm) was mostly observed (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with previous study which also showed that the quantity of water released was 9 more than expected from the dehydroxylation of vermiculite itself [43]. In K-vermiculite, all typical vermiculite features had disappeared and the lattice had drastically collapsed [7]. By the same token, the typical well-ordered mica-like structure reflection at 2θ = 8.74° (10.10 nm) was mostly observed (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The frequency of the shaker was adjusted to 200 rpm (rotations per minute). For these experiments, 50 g of vermiculite were weighed out and enough salt was added to prepare 250 ml of saturated salt solution: vermiculite selectivity rises with increase of the preferred ion loading [7,28]. The ion-exchanged vermiculites were washed thoroughly with distilled water until all chloride anions were quantitatively removed.…”
Section: Experimental: Starting Materials and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…: Na-Cs (Maes and Cremers, 1978); Chambers mont. : Na Cs (Cremers and Thomas, 1968) and Li ~ Na (Gast and Klobe, 1971); hectorite: Na ~ Cs (Maes and Cremers, 1978); Otay mont. : Na ~ K (Shainberg et al, 1987) and Na ~ Cs (Maes and Cremers, 1978); Polkville mont.…”
Section: Cross Validationmentioning
confidence: 99%
“…: Na ~ K (Shainberg et al, 1987) and Na ~ Cs (Maes and Cremers, 1978); Polkville mont. : Na ~ K (Shainberg et al, 1987); Transvaal vermiculite: Na ~ Li (Gast and Klobe, 1971); Utah bentonite: Na ~ K (Tabikh et al, 1959) and Na ~ Rb (Kunishi and Heald, 1968); Upton mont. : Na K (Shainberg et al, 1987); Wyoming bentonite: Na ~ Li (Tabikh et al, 1960).…”
Section: Cross Validationmentioning
confidence: 99%